Economic Adjustment in Low-Income Countries : Experience Under the Enhanced Structural Adjustment Facility - Rozwadowski, F. (Occasional Papers; Occasional Paper ;, 1993)
This paper evaluates progress made under ESAF-supported programs in attaining external viability, restoring economic growth, and implementing structural reforms. Performance is evaluated for 19 countries that entered ESAF arrangements by mid-1992, against the background of their initial conditions, external environment, and implementation of structural and macroeconomic policies.